A Review of AI in Precision Agriculture - Bhojak, Renu; Kumar, Pankaj; Sweta; Jameel, Azlee (International Journal of Psychosocial Rehabilitation, 2020)
Horticulture accommodates the most fundamental necessities of mankind: food and fiber. The presentation of new cultivating methods in the previous hundred years (e.g., during the Green Upset) has helped farming stay up with developing requests for food and other horticultural items. Notwithstanding, further increments in food interest, a developing populace, and rising pay levels are probably going to overwhelm regular assets. With developing acknowledgment of the adverse consequences of agribusiness on the climate, new procedures and approaches ought to be capable of meeting future food requests while diminishing the ecological impression of horticulture. Arising advancements, for example, geospatial innovations, the Web of Things (IoT), huge information investigation, and man-made consciousness (simulated intelligence), could be used to make informed administration choices intended to increment crop creation. Accuracy farming (Dad) involves the use of a set-up of such innovations to streamline farming contributions to increment rural creation and lessen input misfortunes. Utilization of remote detecting advancements for Dad has expanded quickly during the past few years. The exceptional accessibility of high-goal (spatial, phantom, and transient) satellite pictures has advanced the utilization of remote detecting in numerous Dad applications, including crop.